Drones as a tool for the sustainable conservation of heritage metal Struc-tures - Elizalde, Rubén Rodríguez (International Journal of Innovative Research and Scientific Studies, 2025)
Historic infrastructure preservation demands innovative and sustainable methodologies that safeguard structural integrity while minimizing environmental impact. This study ex-plores the application of Remotely Piloted Aircraft Systems (RPAS) for the non-invasive inspection of the Requejo Bridge, a centennial metallic arch bridge that spans the Duero River within a protected natural environment in Spain. Through high-resolution aerial surveys, RPAS technology enabled the exhaustive assessment of areas traditionally difficult to access, identifying localized corrosion and material degradation critical for preventive conservation planning. By eliminating the need for scaffolding and heavy machinery—elements that pose significant ecological risks to sensitive landscapes—the drone-based inspections substantially reduced carbon emissions and resource con-sumption, while optimizing operational costs and minimizing workplace hazards. The findings confirm that RPAS not only enhance the accuracy and efficiency of structural diagnostics but also embody a sustainable maintenance strategy aligned with multiple Sustainable Development Goals (SDGs), including climate action, responsible resource use, and occupational safety. This research advocates for the widespread adoption of drone-assisted methodologies in heritage infrastructure management, offering an envi-ronmentally responsible, economically viable, and safer alternative that extends the ser-vice life of historic structures through proactive and minimally invasive interventions.